2016
DOI: 10.1055/s-0035-1569573
|View full text |Cite
|
Sign up to set email alerts
|

Balloon catheter versus basket catheter for endoscopic bile duct stone extraction: a multicenter randomized trial

Abstract: For extraction of BDSs ≤ 10 mm, complete endoscopic treatment with a single catheter is more likely when choosing a balloon catheter over a basket catheter.University Hospital Medical Information Network Trials Registry: UMIN000011887.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
31
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 13 publications
3
31
1
1
Order By: Relevance
“…Common bile duct stones are treated using a balloon catheter and a basket catheter under ERCP guidance. [1820] However, when large or multiple stones are present in the common bile duct, stone removal may be challenging, even when using endoscopic papillary large balloon dilation. In such cases, EHL under POCS may be useful.…”
Section: Discussionmentioning
confidence: 99%
“…Common bile duct stones are treated using a balloon catheter and a basket catheter under ERCP guidance. [1820] However, when large or multiple stones are present in the common bile duct, stone removal may be challenging, even when using endoscopic papillary large balloon dilation. In such cases, EHL under POCS may be useful.…”
Section: Discussionmentioning
confidence: 99%
“…A multicenter prospective randomized trial demonstrated that the rate of complete stone clearance with a single catheter for CBD stones of ≤10 mm was higher in the balloon catheter group than in the basket catheter group. One study found that there was no significant difference in the rates of PEP and complete stone clearance in one ERCP session between the balloon catheter group and basket catheter group . Mechanical lithotripsy achieves successful stone clearance in 80–90% of patients with difficult CBD stones.…”
Section: Discussionmentioning
confidence: 99%
“…We appreciate the comments made by Dr. Kadayifci regarding our study in which we concluded that complete endoscopic treatment with a single catheter is more likely when choosing a balloon catheter over a basket catheter for the extraction of bile duct stones ≤ 10 mm [1]. In the basket group, the basket catheter was switched to a balloon catheter when the endoscopist had judged the duct clearance to be complete by the basket catheter.…”
mentioning
confidence: 92%